Penerapan PSAK 10 Atas Selisih Kurs Dan Transaksi Mata Uang Asing Pada Laporan Keuangan PT. Amman Mineral Internasional Tbk. - Sabila, Vina; Alfadhila, Dinda; Ramadhani, Nisfi; Rahayu, Saras Tri; Anggriani, Reni; Agustiningsih, Wulandari (Fakultas Ekonomi dan Bisnis Unram, 2024)
In facing the challenges of the current era of business globalization, many companies are involved in international business transactions involving foreign currencies. PSAK No.10 is a statement of Financial Accounting Standards which regulates the effect of changes in foreign currency exchange rates. The purpose of PSAK 10 is to provide guidance on how accounting regulates transactions in foreign currency and overseas business activities in an entity's financial statements, appropriate reporting related to exchange differences is very important to reflect the true value in the company's financial statements. The object of this research is the financial report at PT Amman Mineral Internasional tbk. This research method was carried out by analyzing financial reports using qualitative data analysis techniques. The results of the research show that PT Amman Mineral Intelranasiolnal has implemented PSAK 10 in a collaborative manner in presenting foreign currency transactions in its financial reports. The use of correct exchange rates as well as accurate recording in accordance with accounting standards allows the company to provide reliable and relevant information for users of police reports. spare. Even though most of the company's transactions are denominated in USD, the company still faces significant foreign currency risks from transactions involving Rupiah.